Modern approaches to the formation of ways to motivate work - Alexey Vasilyev; Valeria Litvinova (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет)
The main task of modern enterprise management is to find the most effective methods of personnel management, ensuring the effectiveness of the enterprise as a whole. In such conditions effective system of motivation becomes the most influential factor in increasing the effectiveness of personnel work. Effective motivation promotes creative, productive, intellectual attitude of the employee to his work and directs him to achieve high performance in the organization. That is why every manager in the sphere of personnel management is faced with the question of forming an effective system of personnel work motivation, which would meet the modern conditions of market development and ensure successful operation of the enterprise and its development, as well as development of the whole state economy. Each employee has his personal incentives and motives that induce him to perform certain functions and tasks. In recent decades there has been a change in the management of enterprises, in which the "human factor" has come to be regarded as the main factor in achieving long-term success. Highly qualified, properly organized personnel determine the fate of any enterprise. Creating the concept of motivation at the enterprise it is necessary to find objects of realization of separate types of material and moral stimulation. Each enterprise independently chooses for itself the most appropriate combination of material and socio-psychological incentives of employees to achieve their goals. On the success of this decision depends the speed and possibility of achieving the goals, as well as the effectiveness of both individual employees and enterprises as a whole. However, under the influence of a number of factors, including such factors as the degree of personal responsibility, relationship with the manager, etc., the employee may be disappointed in his work, but the management is interested in employees to be creative and enthusiastic about their duties.